Upscale of sheep and goat community based breeding: Mid term report - Haile, Aynalem; Getachew, Tesfaye (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Presentation in: Midterm Review and Implementation Support Mission. Addis Ababa, Ethiopia, February 7-18, 2022.